Efficacy and safety of Xingnaojing injection for post-operative patients of intracerebral haemorrhage: a meta-analysis and systematic review - Song, Yanbo; Xu, Fangbiao; Li, Shuliang; Sun, Yongkang; Wang, Xinzhi (Frontiers in Pharmacology, 2024)
Background Intracerebral haemorrhage (ICH) is the deadliest subtype of stroke. Surgery remains a vital measure for life-saving in emergency situations, however, the recovery of post-operative patients is not optimistic. This study aimed to evaluate the evidence of the efficacy and safety of Xingnaojing injection (XNJ) for post-operative patients of ICH. Methods From inception to 31 January 2024, we searched eight representative databases for randomized controlled trials on post-operative patients of ICH treated with XNJ. A meta-analysis was conducted using R4.2.2, and the quality of the evidence was evaluated by GRADE criteria. Results The results indicated that the combination of XNJ with conventional western medicine therapy improved the total efficiency rate (RR = 1.26; 95% CI [1.21 to 1.32]; p < 0.0001), reduced the all-cause mortality within 15 days (RR = 0.45; 95% CI [0.30 to 0.67]; p < 0.0001), decreased the volume of hematoma (MD = −4.72; 95% CI [-7.43 to −2.01]; p = 0.0006) and perihematomal edema (MD = −4.11; 95% CI [-8.11 to −0.11]; p = 0.0441), reduced the TNF-α levels (SMD = −1.61, 95% CI [−2.23 to −0.99], p < 0.0001), decreased neurological impairment (SMD = −1.44; 95% CI [-1.78 to −1.11]; p < 0.0001), improved the activities of daily living (SMD = 1.22; 95% CI [0.78 to 1.66]; p < 0.0001), and enhanced the consciousness level (MD = 2.08, 95% CI [1.22 to 2.93], p < 0.0001). In addition, the complications of the combination therapy group were lower (RR = 0.43; 95% CI [0.35 to 0.54]; p < 0.0001) and the adverse drug reactions were comparable to the control group (RR = 0.89; 95% CI [0.55 to 1.45]; p = 0.6521). The trial sequential analysis results showed that the sample size is sufficient. Conclusion Current evidence indicates that XNJ can enhance the efficiency, reduce mortality, and lower the incidence of complications, while demonstrating good tolerability of post-operative patients of ICH. However, the level of evidence from existing studies is relatively weak, and only prove short-term effects, and high-quality RCTs are needed to further verify the accuracy of these conclusions. Systematic Review Registration: identifier (PROSPERO 2024 CRD42024503006). https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024503006, Identifier CRD42024503006.